New York Paper - Heat Requirement and Gas Analysis at Cedar Point Furnace, Port Henry N.Y. - T. F. Witherbee (The American Institute of Mining, Metallurgical, and Petroleum Engineers)
The following calculation of heat requirement covers the working of the furnace from January 25th to February 14th, inclusive. A short time previous to the first date the furnace had been working rather badly, so that 300 lbs. of ore and 500 lbs. of limestone were taken off. Within the time mentioned the quality of the iron passed